Heavy rainfall analysis over Teesta catchment and adjoining areas of Sub-Himalayan West Bengal and Sikkim - G N, RAHA; S, BANDYOPADHYAY; S, DAS (MAUSAM, 2020)
Heavy rainfall (HRF) forecasting in hilly region is always a challenge to the operational forecasters. Synoptic Analogue Model (SAM) is considered as one of the useful tools for HRF forecasting in topographically influenced hilly regions. In every monsoon season, the Teesta river catchment and its adjoining areas in Sub-Himalayan West Bengal and Sikkim (SHWB-S) generally receive several events of HRF. With the primary objective to find the method to issue HRF warning over Teesta river catchment and adjoining areas in SHWB-S, a SAM has been developed by analyzing 18 years (1998-2015) data comprising prevailing synoptic situations affecting the area and daily rainfall data of subsequent day of HRF. In addition, impact of different synoptic systems on the distribution of HRF has also been studied. The results revealed that there exists a good agreement between daily HRF warnings issued with the corresponding HRF event observed over this region on the next day.